Options for Modelling the Financial Viability of Sofix Companies in the Post-crisis Years - Angelov, G. (Економічний вісник Донбасу, 2014)
A financial crisis undoubtedly had the enormous negative operating on the real sector in a national and global scale. A grate number of stopping of companies, business restructuring, decrease of production, and staff surplus. Therefore it is vitally important to estimate financial steady development of the Bulgarian companies. Primary objective of such estimation - to identify accessible possibilities for the acceptance of the adequate, self-weighted decisions, to support companies in the process of adaptation to replacement of market requirements. Aim of the article - to foresee main financial pressures, using models for the estimation of authenticity of bankruptcy of companies and to offer the choice of decisions for overcoming these difficulties. An aim was arrived at through the empiric test of existent models in terms of open corporations of index of SO- FIX during four years, from 2011 to 2014. Results from this test then drawn on as a benchmark test in the process of decision-making. Фінансова криза поза сумнівом мала величезну негативну дію на реальний сектор в національному і глобальному масштабі, у вигляді числа припинень компаній, ділової реструктуризації, убування виробництва, і штабної надмірності. Тому життєво важливо оцінити фінансовий стійкий розвиток Болгарських компаній. Головна мета такої оцінки - ідентифікувати доступні можливості для ухвалення адекватних, зважених рішень, щоб підтримувати компанії в процесі пристосування до заміни ринкових вимог. Мета цієї статті - передбачити головні фінансові труднощі, використовуючи моделі для оцінки вірогідності банкрутства компаній і запропонувати вибір рішень для подолання ці труднощі. Мета досягалася через емпіричне випробування існуючих моделей в термінах відкритих акціонерних товариств індексу SOFIX впродовж чотирьох років, з 2011 до 2014. Результати від цього випробуванняпотім використані як еталонний тест в процесі ух- валення рішення. Финансовый кризис несомненно имел огромное негативное воздействие на реальный сектор в национальном и глобальном масштабе, в виде числа прекращений компаний, деловой реструктуризации, убывания производства, и штабной избыточности. Поэтому жизненно важно оценить финансовое устойчивое развитие Болгарских компаний. Главная цель такой оценки - идентифицировать доступные возможности для принятия адекватных, взвешенных решений, чтобы поддерживать компании в процессе приспосабливания к замене рыночных требований. Цель этой статьи - предсказать главные финансовые трудности, используя модели для оценки вероятностей банкротства компаний и предложить выбор решений для преодоления эти трудности. Цель достигалась через эмпирическое испытание существующих моделей в терминах открытых акционерных обществ индекса SOFIX в течение четырех лет, с 2011 до 2014. Результаты от этого испытания затем использованы как эталонный тест в процессе принятия решения.